A novel compound heterozygous mutation in the arginase-1 gene identified in a Chinese patient with argininemia: A case report. Issue 32 (7th August 2020) - Cui, Dongqing; Liu, Yanxia; Jin, Liang; Hu, Liping; Cao, Lili
Abstract: Introduction: Arginineemia, also known as arginase deficiency, is a rare autosomal recessive metabolic disease. The diagnosis sometimes may be delayed due to atypical clinical manifestations. Confirmation of arginineemia depends on genetic testing. Patient concerns: We reported a Chinese male child presenting with hyperargininemia and progressive spastic diplegia, who has a novel compound heterozygous mutation in the arginase-1 ( ARG1 ) gene (c.263-266delAGAA, p.K88Rfs * 45;c.674T>C, p.L216P), respectively, coming from his mother and father. Diagnosis: The patient was diagnosed with argininemia with a novel compound homozygous mutation of the ARG1 gene at the age of 12 years. Interventions: The patient had a low-protein diet (0.8 g/kg/day). Baclofen, eperisone hydrochloride, botulinum toxin, and rehabilitation training were used to improve his spastic diplegia symptoms for 3 months. Outcomes: The patient's blood arginine was still high after 3 months' low-protein diet. His spastic diplegia symptoms had not aggravated after 3 months' treatment. Conclusions: Argininemia should be considered in a patient with slowly progressive neurologic manifestations, especially spastic diplegia. This case also suggests that tandem mass spectrometry should be used as an effective tool in the validity of neonatal screening for early diagnosis.